2018
DOI: 10.1039/c8ra04451a
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of safe zero valent iron nanoparticles by Myrtus communis leaf extract as an effective agent for reducing excessive iron in iron-overloaded mice, a thalassemia model

Abstract: Green synthesis of Myrtus communis-Zero Valent Iron Nanoparticles (MC-ZVINs) was carried out in an alkaline environment. These nanoparticles were introduced for testing in vivo iron chelation in an ironoverload thalassemia model in mice. The MC-ZVINs were characterized by the use of imaging (electron microscopy) and spectroscopic (UV-vis and infrared absorption, dynamic light scattering and X-ray diffraction) methods. These methods demonstrated that some polyphenols are bound to the surfaces of the MC-ZVINs as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(51 citation statements)
references
References 41 publications
8
42
1
Order By: Relevance
“…From the SEM micrographs obtained (Fig. 5), the synthesized nanoparticles are cubic in nature and have variable sizes as compared to chemical synthesized nanoparticles [15]. This variability in size is due to the inability of the secondary metabolites to control the size of the particles formed as compared to chemical synthesis though phytomediated synthesis is a green approach.…”
Section: Sem Micrographs Of Iron Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the SEM micrographs obtained (Fig. 5), the synthesized nanoparticles are cubic in nature and have variable sizes as compared to chemical synthesized nanoparticles [15]. This variability in size is due to the inability of the secondary metabolites to control the size of the particles formed as compared to chemical synthesis though phytomediated synthesis is a green approach.…”
Section: Sem Micrographs Of Iron Nanoparticlesmentioning
confidence: 99%
“…This variability in size is due to the inability of the secondary metabolites to control the size of the particles formed as compared to chemical synthesis though phytomediated synthesis is a green approach. Since the plant extract contains various secondary metabolites, they act as reducing and stabilizing agents during bio-reduction reaction during the synthesis of metallic nanoparticles [15]. EDX spectrum showed that Fe-P NPs are composed primarily of Fe, O, C, and Cl.…”
Section: Sem Micrographs Of Iron Nanoparticlesmentioning
confidence: 99%
“…The second degradation step centered at 250 °C in DTGA can be linked to the decomposition of the organic layer around the particles. This decomposition makes the main peak in the DTGA curve which has been reported to be present as phyto mediated synthesis of nanoparticles affords them an organic capping layer [33,49].…”
Section: Tga and Dtga Of Iron Nanoparticlesmentioning
confidence: 95%
“…In the case of biological synthesis of nanoparticles, the aqueous metal ions are reduced and as a result a color change is the first qualitative indication that nanoparticles have been formed ( Fig. 1) [33,34]. Variation of the ratio of the extract to the iron solution revealed that the nanoparticles were synthesized when the volume of the extracts to that of the metal ion was high ( Fig.…”
Section: Synthesis Of Iron Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation